Situational analysis in practice mapping relationalities across disciplines - Clarke, Adele E. 1945- (Routledge, 2022)
Situational Analysis (SA) uses analytic maps of the situation, processes and relations identified using approaches pioneered in Grounded Theory. Creator of the method, award-winning sociologist Adele E. Clarke, with Rachel Washburn and Carrie Friese, show how the method can be, and has been, used in a variety of critical qualitative studies.The entirely new second edition of this book offers several chapters on the method and new introductory material from the editors about developments in using SA in qualitative inquiry. Part I introduces readers to the method of SA, discussing recent developments in the field. Part II offers five new chapters about various facets of the SA method, including a history of Grounded Theory and Situational Analysis, SA as critical pragmatist interactionism, using SA in managing a mixed-methods project, and SA mapping in the social policy classroom and in clinical counseling as innovatively collaborative analysis. Part III offers six new exemplary research articles drawn from energy research and international relations, public health research methods, disabled access to public transportation, participation in conservation in a biosphere reserve, and PTSD and the military. Authors' reflections on their experiences in using the method are also included.These carefully selected new readings vividly demonstrate how widely this method has travelled, successfully meeting the needs of diverse researchers seeking an innovative relational approach to critically analyzing a wide array of data. Situational Analysis in Practice will be of interest to undergraduate and graduate students practicing the SA method across the social sciences, including sociology and healthcare among other disciplines, as well as research scholars interested in qualitative inquiry